Developing brain networks of attention. Issue 6 (December 2016) - Posner, Michael I.; Rothbart, Mary K.; Voelker, Pascale
Abstract : Purpose of review: Attention is a primary cognitive function critical for perception, language, and memory. We provide an update on brain networks related to attention, their development, training, and pathologies. Recent findings: An executive attention network, also called the cingulo-opercular network, allows voluntary control of behavior in accordance with goals. Individual differences among children in self-regulation have been measured by a higher order factor called effortful control, which is related to the executive network and to the size of the anterior cingulate cortex. Summary: Brain networks of attention arise in infancy and are related to individual differences, including pathology during childhood. Methods of training attention may improve performance and ameliorate pathology.